Determinação da concentração de metais em cultivares produzidos nos perímetros irrigados Jacarecica I e açude Macela localizados na cidade de Itabaiana-SE - Santos, Marcos Santiago (2012)
The technological development and population growth have led man to increasingly exploit the natural resources of Earth Planet to meet their own needs, which has caused a major concern as the environment, since this operation has not been done so rational, but a predatory way. With population growth, it´s necessary to increase food production, but the area of cropland in the world does not grow as fast as population. Thus, increase of food production becomes possible with intensification of agriculture in the areas available, through the use of inputs such as fertilizers, agrochemicals, fossil energy and irrigation techniques. Currently, one of the most serious problems affecting the environment from chemical pollution is organic or inorganic in nature, resulting from residential and industrial discharges. All forms of life are affected by the presence of heavy metals, ones more and ones less, depending on the dose and chemical form. Thus, the major concern with these elements is related to its bioaccumulation by aquatic flora and fauna that ultimately reach the man, producing lethal and sublethal effects arising from metabolic disorders. The knowledge about the interactions between plants and heavy metals is very important, not only the safety of the environment, but also to reduce the risks associated with the introduction of these elements in the food chain. This study determined the concentration of metals in cultivars produced in irrigated areas Jacarecica I and Macela Dam in Itabaiana-SE. The quantification of metals Zn, Cu, Ni, Cr, Pb, Mn, Fe, Na, K, Mg and Ca was made by Atomic Absorption Spectrometry. The results of the analyzes in vegetables were expressed as a function of wet mass. Of the metals analyzed, compared with the levels established by the Agency for Sanitary Surveillance (ANVISA), all samples of vegetables analyzed had levels below the limit of tolerance. The results for the soil samples collected in each irrigated vegetable plots were compared with the "Guiding Values for Soils and Groundwater in the State of Sao Paulo" the BOARD DECISION No. 195-2005 - E (CETESB, 2005), and all soil samples analyzed had levels below these values. The data set obtained with the mean concentrations of vegetables and soil samples was subjected to exploratory data techniques, principal component analysis (PCA) and hierarchical cluster analysis (HCA) promoting the separation of vegetables according to their type , showing that there is a predominance in metal concentrations in vegetables of roots, while the soil was separated according with the perimeter and the elements in macro and micronutrientes. The computational program Statistica 6.0 was used for processing the data and generation of graphics . The accuracy and precision of the analytical method for samples of vegetables and soils were determined by analyzing, in triplicate, the certified reference material Peach leaf (NIST 1547) and sediment (NCS DC 75304), respectively. The results showed that at the present time, there is no contamination in irrigated areas, for the studied metals.